The Development of Japanese History Teaching Materials With ADDIE Method - Alpina Pamugari; Yosefa Putri Tanjungsari; Ari Artadi; Hari Setiawan (IZUMI, 2020)
Japanese history course is one of the primary supporting knowledge for Japanese language and culture learners to understand Japan as a whole. Therefore, the Japanese Language and Culture department at Darma Persada University, providing a Nihon no Rekishi (Japan History) lecture using Japanese language textbooks of Japan History. However, based on the results of the evaluation using a questionnaire, Japanese language modules that our campus had now does not give a positive impact on student understanding. Based on this, our goal is to make Japanese History module with developing lecture materials. The development of teaching materials in the form of this module is a Research and Development (R&D) research, based on the ADDIE (Analyse, Design, Development, Implementation, Evaluation) method. First, the results of the analyse phase is improvement needed in order to be able to present knowledge that is not only useful and actual but also encourages students to think critically about Japan history. Second, the results at the design stage, a teaching module is prepared, which contains balanced explanations with pictures or mini videos. They can question about pictures or figures or events that have multiple perspectives for discussed with teacher in lectures. Third, in the development stage, based on the results of analysing and design stages with consultations from leading universities in Japan experts found that at the development stage, have the results that the implementation and evaluation contents of the module are a simplification of reference literature materials, and provide several perspectives on figures and events in Japanese history.